ANALISIS PEMANFAATAN BERBAGAI MEDIA PEMBELAJARAN DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL PADA MATERI KEGIATAN EKONOMI KELAS V SEKOLAH DASAR: KAJIAN LITERATUR - Isna Aniqotun Nada; Tasya Permata Islami; Mirza Mutiara Maulisa Insani; Reva Amelia; Priyono Tri Febrianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This literature review analyzes the use of various learning media in Social Studies learning, especially the economic activities topic in grade V elementary school. The study aims to identify the dominant media types, describe their pedagogical strengths, and formulate recommendations for media selection that fit the characteristics of economic activities content. The review employed a descriptive qualitative literature review by examining 15 Indonesian-language journal articles published from 2020 to 2025. The selected studies were analyzed through reduction, categorization, comparison, and synthesis of findings. The results indicate that visual media, audio-visual media, contextual video, posters, interactive multimedia, technology-based media, and local-culture-based media consistently support learning motivation, conceptual understanding, and student engagement in Social Studies. For economic activities content, the most relevant media are those that visualize processes, present concrete examples from students’ surroundings, and encourage active discussion and observation. The study concludes that no single medium is universally superior; effectiveness depends on the alignment among learning objectives, learner characteristics, classroom conditions, and the sequence of learning activities.